Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.

Exome sequencing identifies novel missense and deletion variants in RTN4IP1 associated with optic atrophy, global developmental delay, epilepsy, ataxia, and choreoathetosis. - D'Gama, Alissa M; England, Eleina; Madden, Jill A; Shi, JiAHi; Chao, Katherine R; Wojcik, Monica H; Torres, Alcy R; Tan, Wen-Hann; Berry, Gerard T; Prabhu, Sanjay P; Agrawal, Pankaj B (Am J Med Genet A, 2021)
Inherited optic neuropathies (IONs) are neurodegenerative disorders characterized by optic atrophy with or without extraocular manifestations. Optic atrophy-10 (OPA10) is an autosomal recessive ION recently reported to be caused by mutations in RTN4IP1, which encodes reticulon 4 interacting protein 1 (RTN4IP1), a mitochondrial ubiquinol oxydo-reductase. Here we report novel compound heterozygous mutations in RTN4IP1 in a male proband with developmental delay, epilepsy, optic atrophy, ataxia, and choreoathetosis. Workup was notable for transiently elevated lactate and lactate-to-pyruvate ratio, brain magnetic resonance imaging with optic atrophy and T2 signal abnormalities, and a nondiagnostic initial genetic workup, including chromosomal microarray and mitochondrial panel testing. Exome sequencing identified a paternally inherited missense variant (c.263T>G, p.Val88Gly) predicted to be deleterious and a maternally inherited deletion encompassing RTN4IP1. To our knowledge, this is the first report of a non-single nucleotide pathogenic variant associated with OPA10. This case highlights the expanding phenotypic spectrum of OPA10, the association between "syndromic" cases and severe RTN4IP1 mutations, and the importance of nonbiased genetic testing, such as ES, to analyze multiple genes and variants types, in patients suspected of having genetic disease.

Congenital Heart Defects Due to Missense Variants. - Morton, Sarah U; Agarwal, Radhika; Madden, Jill A; Genetti, Casie A; Brownstein, Catherine A; López-Giráldez, Francesc; Choi, Jungmin; Seidman, Christine E; Seidman, Jonathan G; Lyon, Gholson J; Agrawal, Pankaj B (Circ Genom Precis Med, 2020)

De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Deciphering congenital anomalies for the next generation. - Wojcik, Monica H; Agrawal, Pankaj B (Cold Spring Harb Mol Case Stud, 2020)
Congenital anomalies are common, with 2%-3% of infants estimated to have at least one major congenital malformation and countless others with minor malformations of lesser cosmetic or medical importance. As congenital malformations are major drivers of morbidity and mortality, representing the leading cause of infant mortality in the United States, there is substantial interest in understanding the underlying etiologies-particularly if modifiable causes may be identified or pre- or postnatal treatments can be offered. Recent research has begun to reveal the spectrum of monogenic disorders that commonly result in birth defects, and newer approaches have revealed non-Mendelian genetic contributions including gene-environment interactions. Our experience suggests that increased efforts to sequence and analyze cases of perinatal death, as well as continued global collaboration, will be essential in understanding the genomic landscape of structural anomalies.
Keywords: Congenital Abnormalities; Family Characteristics; Female; Humans; Infant; Pregnancy

Genetic diagnosis in the fetus. - Wojcik, Monica H; Reimers, Rebecca; Poorvu, Tabitha; Agrawal, Pankaj B (J Perinatol, 2020)
Many genetic disorders are detectable in the prenatal period, and the capacity to identify them has increased remarkably as molecular genetic testing techniques continue to improve and become incorporated into clinical practice. The indications for prenatal genetic testing vary widely, including follow-up of an anomaly found by routine ultrasound or maternal aneuploidy screening, a family history of genetic disease, advanced maternal or paternal age, or evaluation of a low-risk pregnancy due to parental concern. The interpretation of genetic variants identified in the prenatal period poses unique challenges due to the lack of ability for deep phenotyping as well as the option to make critical decisions regarding pregnancy continuation and perinatal management. In this review, we address the various modalities currently available and commonly used for genetic testing, including preimplantation genetic testing of embryos, cell-free DNA testing, and diagnostic procedures such as chorionic villous sampling, amniocentesis, or percutaneous umbilical blood sampling, from which samples may be sent for a wide variety of genetic tests. We discuss the difference between these modalities for the genetic diagnosis of a fetus, their strengths and weaknesses, and strategies for their optimal use in order to direct perinatal care.

Prenatal Diagnosis of a Ventral Abdominal Wall Defect. - Beam, Kristyn; Wojcik, Monica H; Agrawal, Pankaj B; Smithers, Charles; Estroff, Judy (Neoreviews, 2020)
Keywords: Abnormalities, Multiple; Echocardiography; Fatal Outcome; Female; Hernia, Abdominal; Hernia, Diaphragmatic; Hernia, Ventral; Humans; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prenatal Diagnosis; Ultrasonography, Prenatal

Genome Sequencing Identifies the Pathogenic Variant Missed by Prior Testing in an Infant with Marfan Syndrome. - Wojcik, Monica H; Thiele, Katri; Grant, Carly F; Chao, Katherine; Goodrich, Julia; O'Donnell-Luria, Anne; Lacro, Ronald V; Tan, Wen-Hann; Agrawal, Pankaj B (J Pediatr, 2019)
We describe an infant with a phenotype typical of early onset Marfan syndrome whose genetic evaluation, including Sanger sequencing and deletion/duplication testing of FBN1 and exome sequencing, was negative. Ultimately, genome sequencing revealed a deletion missed on prior testing, demonstrating the unique utility of genome sequencing for molecular genetic diagnosis.

Infant mortality: the contribution of genetic disorders. - Wojcik, Monica H; Schwartz, Talia S; Thiele, Katri E; Paterson, Heather; Stadelmaier, Rachel; Mullen, Thomas E; VanNoy, Grace E; Genetti, Casie A; Madden, Jill A; Gubbels, Cynthia S; Yu, Timothy W; Tan, Wen-Hann; et al. (J Perinatol, 2019)
OBJECTIVE: To determine the proportion of infant deaths occurring in the setting of a confirmed genetic disorder. STUDY DESIGN: A retrospective analysis of the electronic medical records of infants born from 1 January, 2011 to 1 June, 2017, who died prior to 1 year of age. RESULTS: Five hundred and seventy three deceased infants were identified. One hundred and seventeen were confirmed to have a molecular or cytogenetic diagnosis in a clinical diagnostic laboratory and an additional seven were diagnosed by research testing for a total of 124/573 (22%) diagnosed infants. A total of 67/124 (54%) had chromosomal disorders and 58/124 (47%) had single gene disorders (one infant had both). The proportion of diagnoses made by sequencing technologies, such as exome sequencing, increased over the years. CONCLUSIONS: The prevalence of confirmed genetic disorders within our cohort of infant deaths is higher than that previously reported. Increased efforts are needed to further understand the mortality burden of genetic disorders in infancy.

Novel SPEG mutations in congenital myopathies: Genotype-phenotype correlations. - Qualls, Anita E; Donkervoort, Sandra; Herkert, Johanna C; D'Gama, Alissa M; Bharucha-Goebel, Diana; Collins, James; Chao, Katherine R; Foley, A Reghan; Schoots, Mirthe H; Jongbloed, Jan D H; Bönnemann, Carsten G; Agrawal, Pankaj B (Muscle Nerve, 2019)
INTRODUCTION: Centronuclear myopathies (CNMs) are a subtype of congenital myopathies (CMs) characterized by muscle weakness, predominant type 1 fibers, and increased central nuclei. SPEG (striated preferentially expressed protein kinase) mutations have recently been identified in 7 CM patients (6 with CNMs). We report 2 additional patients with SPEG mutations expanding the phenotype and evaluate genotype-phenotype correlations associated with SPEG mutations. METHODS: Using whole exome/genome sequencing in CM families, we identified novel recessive SPEG mutations in 2 patients. RESULTS: Patient 1, with severe muscle weakness requiring respiratory support, dilated cardiomyopathy, ophthalmoplegia, and findings of nonspecific CM on muscle biopsy carried a homozygous SPEG mutation (p.Val3062del). Patient 2, with milder muscle weakness, ophthalmoplegia, and CNM carried compound heterozygous mutations (p.Leu728Argfs*82) and (p.Val2997Glyfs*52). CONCLUSIONS: The 2 patients add insight into genotype-phenotype correlations of SPEG-associated CMs. Clinicians should consider evaluating a CM patient for SPEG mutations even in the absence of CNM features. Muscle Nerve 59:357-362, 2019.
Keywords: Biopsy; Child; Child, Preschool; Consanguinity; Exome; Female; Genetic Association Studies; Humans; Infant; Male; Muscle Proteins; Muscle Weakness; Muscle, Skeletal; Mutation; Myopathies, Structural, Congenital; Protein-Serine-Threonine Kinases; Sequence Analysis

Unique bioinformatic approach and comprehensive reanalysis improve diagnostic yield of clinical exomes. - Schmitz-Abe, Klaus; Li, Qifei; Rosen, Samantha M; Nori, Neeharika; Madden, Jill A; Genetti, Casie A; Wojcik, Monica H; Ponnaluri, Sadhana; Gubbels, Cynthia S; Picker, Jonathan D; O'Donnell-Luria, Anne H; Yu, Timothy W; et al. (Eur J Hum Genet, 2019)
Clinical exome sequencing (CES) is increasingly being utilized; however, a large proportion of patients remain undiagnosed, creating a need for a systematic approach to increase the diagnostic yield. We have reanalyzed CES data for a clinically heterogeneous cohort of 102 probands with likely Mendelian conditions, including 74 negative cases and 28 cases with candidate variants, but reanalysis requested by clinicians. Reanalysis was performed by an interdisciplinary team using a validated custom-built pipeline, "Variant Explorer Pipeline" (VExP). This reanalysis approach and results were compared with existing literature. Reanalysis of candidate variants from CES in 28 cases revealed 1 interpretation that needed to be reclassified. A confirmed or potential genetic diagnosis was identified in 24 of 75 CES-negative/reclassified cases (32.0%), including variants in known disease-causing genes (n = 6) or candidate genes (n = 18). This yield was higher compared with similar studies demonstrating the utility of this approach. In summary, reanalysis of negative CES in a research setting enhances diagnostic yield by about a third. This study suggests the need for comprehensive, continued reanalysis of exome data when molecular diagnosis is elusive.

Heterozygous De Novo UBTF Gain-of-Function Variant Is Associated with Neurodegeneration in Childhood. - Edvardson, Simon; Nicolae, Claudia M; Agrawal, Pankaj B; Mignot, Cyril; Payne, Katelyn; Prasad, Asuri Narayan; Prasad, Chitra; Sadler, Laurie; Nava, Caroline; Mullen, Thomas E; Begtrup, Amber; Baskin, Berivan; et al. (Am J Hum Genet, 2017)
Ribosomal RNA (rRNA) is transcribed from rDNA by RNA polymerase I (Pol I) to produce the 45S precursor of the 28S, 5.8S, and 18S rRNA components of the ribosome. Two transcription factors have been defined for Pol I in mammals, the selectivity factor SL1, and the upstream binding transcription factor (UBF), which interacts with the upstream control element to facilitate the assembly of the transcription initiation complex including SL1 and Pol I. In seven unrelated affected individuals, all suffering from developmental regression starting at 2.5-7 years, we identified a heterozygous variant, c.628G>A in UBTF, encoding p.Glu210Lys in UBF, which occurred de novo in all cases. While the levels of UBF, Ser388 phosphorylated UBF, and other Pol I-related components (POLR1E, TAF1A, and TAF1C) remained unchanged in cells of an affected individual, the variant conferred gain of function to UBF, manifesting by markedly increased UBF binding to the rDNA promoter and to the 5'- external transcribed spacer. This was associated with significantly increased 18S expression, and enlarged nucleoli which were reduced in number per cell. The data link neurodegeneration in childhood with altered rDNA chromatin status and rRNA metabolism.
Keywords: Adolescent; Adult; Atrophy; Brain; Brain Diseases; Cell Nucleolus; Child; Chromatin; DNA-Binding Proteins; Female; Humans; Male; Neurodegenerative Diseases; Pol1 Transcription Initiation Complex Proteins; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; RNA, Ribosomal, 18S; Young Adult